Physical distancing and use of face masks during school physical activity in covid-19 pandemic: a brief communication - Azócar-Gallardo, Jairo (2021)
In order to reduce the transmission of the Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2) virus that generates coronavirus disease 2019 (COVID-19) globally, governments have adopted multiple health policies. Among the main potential measures for decreasing the risk of contagion include physical or social distancing set at 1.5 m and the use of face masks. However, this suggested physical distance is not recommended during sports practice. On the other hand, the World Health Organization does not recommend the use of face masks during physical activity in adults and children. In addition, with the return to classroom lessons and especially school physical activity may involve a higher risk of contagion when considering the improvised displacements and if it is performed in confined spaces. Therefore, the present communication aims to examine the evidence on the recommended physical or social distancing during school physical activity and on the use of face masks during school physical activities.